The differential effects of prison contact on parent–child relationship quality and child behavioral changes. Issue 3 (26th May 2020) - Haverkate, Danielle L.; Wright, Kevin A.
ABSTRACT: The children of prisoners can suffer from behavioral issues, poor school performance, and heightened risk of crime and delinquency. Separation is part of what makes incarceration a punishment, but what can be done to ensure that it has the least harmful effect on children? Using data from the Arizona Prison Visitation Project, the current study seeks to examine the influence of different types of prison contact (inperson, mail, and phone) and frequency of contact on parent-child relationship quality and how those changes in relationship quality may influence child behavior. Examining results from the parent (n = 127) and child (n = 293) level, the study finds that in-person visitation can increase relationship quality, with mail and frequent phone contact also beneficial.